MEKANISME KOPING DENGAN PRESTASI BELAJAR MAHASISWA SISTEM PEMBELAJARAN BLOK ANGKATAN 2013 - Simarmata, Grace Epyfania; Lestari, Dhian Ririn; Setiawan, Herry (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2015)
Dealing with various demands in learning process makes students fear of the decline in theirlearning achievement, so as the students perform an action to cope with it, which is called coping.The purpose of this study was to find out the relationship between coping mechanism and learningachievement of students with block learning system batch 2013 of nursing program, faculty ofmedicine Lambung mangkurat University Banjarbaru. This study was used analytic descriptive withcross sectional design. The data were collected by means of a questionnaire. The number ofrespondents was 57 persons selected by a total sampling technique. The results of the statisticalanalysis using the Pearson correlation test indicated that there was a significantly positiverelationship between the coping mechanism and the learning achievement of students with blocklearning system batch 2013 of Nursing Program, Faculty of Medicine Lambung MangkuratUniversity Banjarbaru.